Science and innovation for resilient food systems in fragile and conflict-affected settings - CGIAR (CGIAR, 2025)
Scientific advancements and innovative partnerships are transforming food, land, and water systems in fragile and conflict-affected settings (FCAS). By 2030, two-thirds of the world’s extreme poor will live in FCAS, facing compounding crises of climate change, conflict, displacement, and resource scarcity. They represent a critical frontier for CGIAR science—demanding urgent action while precluding science-as-usual. Addressing these challenges requires a paradigm shift—from short-term humanitarian aid to integrated, resilience-building strategies that foster self-sustaining, climate-adaptive food systems. The Food Frontiers and Security (FFS) Science Program addresses these issues by combining CGIAR’s research and scientific innovations with established development partners, NGOs, governments, and the private sector. Panel discussions with partners working in FCAS will bring to the forefront: Cutting-edge CGIAR innovations in food security, seed systems, and climate resilience tailored for crisis-affected communities The power of partnerships across the Humanitarian-Development-Peace (HDP) nexus, featuring collaborations with WFP, UNHCR, NGOs, local governments, and private sector actors Scalable approaches to ensure that evidence-based solutions reach vulnerable populations—reducing dependency on food aid and improving natural resource sustainability, while promoting long-term economic stability Join leading experts from the research, humanitarian response, and development sectors as they share real-world success stories, challenges, and opportunities for scaling scientific solutions to fragility and conflict-driven food insecurity. Through these discussions, we will identify pathways for moving from fragility to stability—leveraging science to build more resilient, inclusive, and sustainable food, land, and water systems in the world's most vulnerable regions. Session objective: To facilitate dialogue on how CGIAR research and innovation can address humanitarian challenges in fragile and conflict-affected settings, strengthening food security and climate resilience through science-driven solutions